Design of a Desktop Application System for Sales Data and Inventory Management at CV Eat Cipeng Jatijajar - Syamsul Bakhri; Yogi Ridho Syahputro (International Journal of Science and Environment (IJSE), 2026)
CV Eat Cipeng Jatijajar is a culinary business that currently relies on manual methods for recording and managing inventory and sales data. This situation leads to various issues, such as time inefficiency, a high risk of recording errors, and difficulties in generating reports. This study aims to design and develop a desktop application—built using Java and MySQL—to facilitate the computerized management of inventory and sales data. The software development process follows the waterfall model, spanning from requirements analysis to black-box testing. Implementation results demonstrate that the developed application enhances operational efficiency, minimizes recording errors, and accelerates data retrieval and reporting processes. The application also features user login capabilities, master data management, tracking of incoming and outgoing goods, order processing, and comprehensive inventory reporting. Consequently, the system is expected to support the company's operations more effectively and professionally.